Individual performance, leadership succession, organizational climate and moderating effect of trust: Data screening and preliminary analysis - Badara, Abdulkadir Musa; Johari, Husna; Tan, Fee Yean (MCSER-Mediterranean Center of Social and Educational Research, 2015)
The main objective of this paper is to present individual performance, leadership succession, organizational climate and moderating effect of trust, data screening processes in the Nigerian commercial banks.Data of the study were collected through research assistant employed, in which 600 questionnaire were sent to employees of the commercial banks.Data were analyzed using Statistical Package for Social Science (SPSS) version 20.Thus, response rate and non-respond biased were ascertained, data cleaning, detection of missing data, treatment of univariate and multivariate outliers and descriptive statistics and correlation. The result revealed that the data is suitable for further analysis.